Boost Converter Based 3-phase AC-AC Active Tracking Voltage Regulator Controlled by a Robust Hybrid Control Method - Felix Hımmelstoss; Faruk Yalçın (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, a switch-mode three-phase active tracking AC-AC voltage regulator based on the boost converter is proposed with a moderate number of active and passive elements used in the topology. A robust hybrid control, where a novel designed feedforward controller supports the closed-loop PID controller, is proposed for the control of the regulator apart from similar studies in the literature. Active tracking response of the reference output phase voltages is augmented by the proposed hybrid control method. Thus nearly close to sine-wave output phase voltages can be obtained, whether the input AC phase voltages are ideal pure sine or not. Also, the modular structure of the regulator topology enables independent control for each output phase. Thus, the supply of balanced/unbalanced wye-connected three-phase loads or independent single-phase loads with nearly close to ideal sine wave voltages can be achieved by the modularity of the regulator. Both experimental and simulation test studies are performed for the proposed regulator system. A laboratory set-up for the regulator is designed for 0-200 Vp input phase voltages (50 Hz), and 0-300 Vp output phase voltages, and 1.8 kW output power. The achieved results for both simulation and experimental tests verify the proposed switch-mode boost-type regulator’s ability to provide output phase voltages nearly close to sine wave with total harmonic distortion (THD) values under 5%.